Penggunaan Kata Umum Dalam Pendaftaran Merek Pada Sengketa Merek STRONG Antara Hardwood Private Limited Dengan PT. Unilever Indonesia, Tbk. Berdasarkan Undang-Undang No. 20 Tahun 2016 Tentang Merek Dan Indikasi Geografis - Fetrya Salsabilla Hanjani; Miranda Risang Ayu Palar; Helitha Novianty Muchtar (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
There are provisions regarding trademarks that cannot be registered in Law No. 20 Year 2016, one of which is in Article 20 letter f which states that "Trademarks cannot be registered if they are common names and/or symbols of public property." However, even though there is already a regulation regarding the invalidity of registration of the use of common words in trademarks, there are still many uses of common words as trademarks in Indonesia. This shows that there is still a lack of clarity regarding the parameters of acceptable use of generic words in trademark registration. One of the famous trademark infringement cases using a common word in Indonesia is the case between PT Unilever Indonesia, Tbk. against Hardwood Private Limited with the alleged use of the "STRONG" Trademark with the Supreme Court Decision Number 332 K/Pdt.Sus- IPR/2021. This research aims to discuss the legal action in the settlement of infringement of well-known trademarks that use the word general and the judge's consideration of infringement of well-known trademarks that use the word general based on Indonesian positive law. Based on the research results, the word "STRONG" is an English word that has a strong meaning. Then the word STRONG is a general or generic word that when referring to the explanation in Article 20 of Law No. 20 Year 2016, the word "STRONG" should not be registered as a trademark because it is a common word